Genomic and Fermentation Characterization of Kluyveromyces marxianus and Saccharomyces cerevisiae in Root Extract-Based Low-Alcohol Beverage - Eun-Ju Lee; Seung-Hyun Choi; Min-Ju Seo; A-Reum Lee; Chan-Song Jang; Woong-Kwon Kwak; Jung-Ki Kwak; Jae-Ho Lee; Won-Joo Yoon; Seok-Min Yoon (Fermentation, 2025)
Fermentation is widely recognized for enhancing the sensory attributes and nutritional value in foods, with recent research focusing on non-alcoholic and root-based functional beverages. In this study, the genomic and fermentation characteristics of Kluyveromyces marxianus LRCC8279 (KM8279) and Saccharomyces cerevisiae LRCC8293 (SC8293) were analyzed, specifically for their application in root extract-based low-alcohol fermentations. Whole-genome sequencing revealed that both strains harbored key genes involved in glucose, fructose, and sucrose metabolism and genes implicated in ethanol production. Although SC8293 harbored maltose-metabolizing genes, including MAL13 and MAL31, these genes were absent in KM8279. This genetic difference was evident in the fermentation performance, manifesting as distinct variations in alcohol production depending on the carbohydrate source. A further investigation of fermentation conditions demonstrated that both strains maintained low alcohol levels and exhibited a consistent growth at 15–20 °C within 72 h. Fermentation using extracts from Pueraria lobata, Arctium lappa (AL), Zingiber officinale (ZO), and Platycodon grandifloras revealed that KM8279 markedly increased the production of volatile compounds, contributing to floral and fruity sensory attributes in ZO and AL, whereas SC8293 contributed to a more complex flavor profile in AL. Notably, KM8279-ZO and KM8279-AL fermentations maintained alcohol contents below 1%, indicating their potential application in non-alcoholic beverages. Future studies are needed to investigate the relationship between the key volatile compound production and associated genetic characteristics, along with sensory evaluations, to develop optimized flavor modulation strategies.